1991
DOI: 10.1037/0022-3514.61.2.195
|View full text |Cite
|
Sign up to set email alerts
|

Ease of retrieval as information: Another look at the availability heuristic.

Abstract: Experienced ease of recall was found to qualify the implications of recalled content. Ss who had to recall 12 examples of assertive (unassertive) behaviors, which was difficult, rated themselves as less assertive (less unassertive) than subjects who had to recall 6 examples, which was easy. In fact, Ss reported higher assertiveness after recalling 12 unassertive rather than 12 assertive behaviors. Thus, self-assessments only reflected the implications of recalled content if recall was easy. The impact of ease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

42
781
5
10

Year Published

1999
1999
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,178 publications
(863 citation statements)
references
References 31 publications
42
781
5
10
Order By: Relevance
“…The latter typically cannot be traced exclusively to one specific source. Such an interpretation of their results also conforms with evidence indicating that in making inferences people appear to rely less on subjective assessments of memory (e.g., processing fluency) when they can attribute this memory to the experiment than when such an explicit attribution is impossible (e.g., Jacoby, Kelley, Brown, & Jasechko, 1989;Oppenheimer, 2004;Schwarz et al, 1991).…”
Section: The Noncompensatory Status Of Recognition Informationsupporting
confidence: 84%
“…The latter typically cannot be traced exclusively to one specific source. Such an interpretation of their results also conforms with evidence indicating that in making inferences people appear to rely less on subjective assessments of memory (e.g., processing fluency) when they can attribute this memory to the experiment than when such an explicit attribution is impossible (e.g., Jacoby, Kelley, Brown, & Jasechko, 1989;Oppenheimer, 2004;Schwarz et al, 1991).…”
Section: The Noncompensatory Status Of Recognition Informationsupporting
confidence: 84%
“…For example, past research has shown that individuals hold their attitudes with greater certainty when they perceive it was easy to generate thoughts in favor of their attitudes and difficult to generate thoughts against their attitudes (e.g., Haddock, Rothman, Reber, & Schwarz, 1998;Haddock, Rothman, & Schwarz, 1996;Schwarz et al, 1991). In one relevant study, Haddock, Rothman, and Schwarz (1996) instructed participants to generate either three or seven favorable or unfavorable thoughts in response to a position they supported.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, if we ask participants to produce either one or three explanations for a (known) surprising outcome, their metacognitive sense should be that more cognitive work is required for the latter over the former and, consequently, even though they are still explaining the occurrence of the outcome, they will perceive the latter outcomes to be more surprising than the former (this manipulation is analogous to one used in the hindsight bias literature; see, e.g., Schwarz, Bless, Strack, Klumpp, Rittenauer-Schatka & Simons, 1991). Furthermore, it should be stressed that this "number-of-explanations" effect should only hold for known surprising outcomes, not for less-known outcomes, because known outcomes have a ready supply of possible explanations, whereas less-known outcomes do not.…”
Section: Experiments 5: Effects Of Explanation Task On Surprise Judgmentsmentioning
confidence: 99%